Profitability Ratio Analysis To Measure Financial Performance (PT. Astra International Tbk 2020-2023) - Yulianti, Nopi; Sutarsa , Monika; Fitriani, Rani Ligar (Science Tech Group, 2025)
This research examines the financial performance of PT Astra International Tbk over a four-year period from 2020 to 2023, with a specific focus on profitability metrics. The study employs quantitative analysis through a descriptive approach, utilizing key profitability ratios including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Gross Profit Margin (GPM), and Operating Profit Margin (OPM). By comparing these performance indicators against established industry benchmarks, the research provides a comprehensive assessment of the company's financial health and efficiency. Findings reveal mixed results: ROA averaged 8.05% and ROE averaged 13.92%, both falling below industry standards, indicating suboptimal asset and equity utilization. Similarly, GPM averaged 22.6%, below the recommended threshold for satisfactory performance. However, NPM and OPM averaged 14.05% and 15.06% respectively, exceeding minimum industry standards and suggesting favorable revenue management and operational efficiency. This analysis offers valuable insights for stakeholders and management to identify areas for strategic improvement in Astra International's financial operations.